Mobile application: learning basic mathematics operation using augmented reality / Mohamad Harith Azfar Mohamad Hatta ... [et al.] - Mohamad Hatta, Mohamad Harith Azfar; Nasrudin, Nur Hasni; Azmi, Anis Zafirah; Ahmad Junid, Rosida (2020)
In school, students need to learn mathematics not only for taking the exam but also can use their knowledge to solve the problem in daily life. When students are dealing with numerical information, they tend to have a negative feeling or fear, and this situation is known as mathematics anxiety. This aim of the project is to develop a mobile application to learn basic mathematics operation by applying augmented reality and to evaluate the technology acceptance of the mobile application. This project implements a mobile application that has augmented reality technology. This project split into 5 phases in methodology: planning, design, analysis, implementation and testing. The user requirement is gathered from the interview with the teachers. This mobile application is implemented by using Unity. The software development kit (SDK) for making the augmented reality in Unity is by using Vuforia.